Medicolegal and Ethical Perspectives in the Use of Narcoanalysis in Criminal Investigations in India - Vina Vaswani; Venkatkrishna Shenoy; Akuma Ifeanyichukwu (Archives of Medicine and Health Sciences)
This article delves into the strengths and weaknesses of the use of narcoanalysis in criminal investigation in India, from a forensic lens, also bringing with it ethical perspectives. The article shows the interconnectedness of forensic medicine, ethics, and narcoanalysis highlighting the intricate relationship between scientific investigation and ethicolegal processes in the pursuit of truth in criminal cases. The use of narcoanalysis in crime investigation may be less harmful but there is a significant amounts of mental coercion. The article concludes that the interconnectedness collectively contributes to the quest for justice; however, emphases are placed on the importance of adhering to ethical standards and respecting individual rights.